Experimental Validation of a Mitigation Method of Ferranti Effect in Transmission Line - Tareq Foqha (17947778) (2023)
Electric power transmission networks should be operated in efficient, safe, and reliable conditions. To improve the stability and transfer capability of power transmission, it is necessary to mitigate the Ferranti effect. This paper investigates the impact of increasing the length of the transmission line on its receiving end voltage under no-load conditions. A variable shunt reactor compensation for transmission lines is used to control the voltage level at different lengths of the transmission line. The proposed method demonstrates that the value of the shunt reactor required to maintain the receiving end voltage can be estimated. Moreover, the system is modeled using the PowerWorld simulator, and the effectiveness of the proposed model has been verified by experimental results. The experimental results demonstrate the efficiency of the proposed methodology and match the simulation results, which are then validated by simulating the WSCC 9-bus and IEEE 30-bus test systems. Other Information Published in: IEEE Access License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3244826